(untitled) (Research, Society and Development, 2024)
The deleterious effects of reducing the water availability of crops can be minimized by increasing nitrogen fertilization. This study proposes to investigate the effects of variable water conditions on the soil on the sunflower cultivar Charrua and whether the increase in nitrogen fertilization can mitigate these effects. The design used was that of randomized blocks, analyzed in a 4x2x3 factorial scheme with 3 repetitions, with factor A (RH - water replacements of 25, 50, 75 and 100% of available water capacity), factor B (DN - 100 and 200% of the recommended nitrogen fertilization) and factor C (EP - Period of evaluation - 20, 30, 50 and 70 days after sowing) for growth analysis and 90 days for dry matter and production. Growth was evaluated by plant height (AP), stem diameter (DC), number of leaves (NF) and leaf area (AF). In production, we analyzed chapter dry weight (MSCAP), leaf dry weight (MSF), stem dry weight (MSC), 100 grain weight (M100G), total grain weight (MGTotal), the total number of grains (NGTotal) and the number of viable grains (NGV). The production of dry pasta; mass and total number of achenes, as well as the number of viable achenes responded linearly only with RH. Further studies are needed in order to elucidate the decreases that occurred in CD and PA that occurred due to the increase in DN.